System for ensuring the financial security of the enterprise - Azarenkova , Galyna; Vepretska , Sofiia (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2024)
The aim of this study is to conduct a retrospective and current analysis of scientific publications on the issues of managing the financial security system of an enterprise, its optimization and improvement at the international level, based on the use of the Scopus scientometric database, the formation of a map of interconnections with other sciences and lexemes, and the creation of cluster maps using the VOSviewer v.1.6.15 tool. The main focus of the research is on identifying the relationships between the key concepts of "financial security," "finance," and "financial security system," as well as determining their theoretical and methodological foundations in the context of enterprise activities. The obtained results can be used to improve the financial security systems of enterprises and integrate them into the overall corporate governance system. The research conclusions emphasize the need to comply with legislative requirements and ethical standards in the financial sector. Additionally, the results may contribute to the development of new approaches to creating financial security standards, ensuring stability and reliability for enterprises in a changing economic environment.